"It's Huge, in a Way." Conflicting Stakeholder Priorities for Managing Hearing Impairment for People Living with Dementia in Residential Aged Care Facilities. Issue 4 (8th August 2022) - Bott, Anthea; Meyer, Carly; Hickson, Louise; Pachana, Nancy A.
ABSTRACT: Objectives: The aims of this study were to a) explore the impact of hearing impairment on people living with dementia in residential aged care facilities (RACFs) and b) investigate management of hearing impairment for this population. Methods: A descriptive qualitative approach, consisting of semi-structured interviews, was conducted with 23 participants across four stakeholder groups (audiologists, care staff, family members and individuals with dementia and hearing impairment living in RACFs). Results: Thematic analysis revealed an overarching theme of "different priorities for managing hearing impairment" that emerged from the data. Audiologists and care staff prioritized different practices for managing hearing impairment: audiologists emphasized hearing aids and care staff emphasized communication strategies. Care staff also identified that current management of hearing impairment was sub-optimal as they do not prioritize managing it. Conclusions: Residents with dementia and hearing impairment living in RACFs are not receiving optimal hearing management. Further research is required to understand the factors that influence this. Clinical implications: Changes in practices of both care staff and audiologists are required to improve hearing impairment management for this population.